Egg laying rather than host quality or host feeding experience drives habitat estimation in the parasitic wasp Nasonia vitripennis - Koppik, Mareike; Thiel, Andra; Hoffmeister, Thomas S. (Dryad, 2020)
In variable environments, sampling information on habitat quality is
essential for making adaptive foraging decisions. In insect parasitoids,
females foraging for hosts have repeatedly been shown to employ behavioral
strategies that are in line with predictions from optimal foraging models.
Yet, which cues exactly are employed to sample information on habitat
quality, has rarely been investigated. Using the gregarious parasitoid
Nasonia vitripennis (Walker) (Hymenoptera: Pteromalidae), we provided
females with different cues about hosts to elucidate, which of them would
change a wasp’s posterior behavior suggesting a change in information
status. We employed posterior clutch size decisions on a host as proxy for
a female’s estimation of habitat quality. Taking into account changes in
physiological state of the foraging parasitoid, we tested whether
different host qualities encountered previously change the subsequent
clutch size decision in females. Additionally, we investigated whether
other kinds of positive experiences - such as ample time to investigate
hosts, host feeding, or egg laying  - would increase a wasp’s
estimated value of habitat quality. Contrary to our expectations, quality
differences in previously encountered hosts did not affect clutch size
decisions. However, we found that prior egg laying experience changes
posterior egg allocation to a host, indicating a change in female
information status. Host feeding and the time available for host
inspection, though correlated with egg laying experience, did not seem to
contribute to this change in information status.
Keywords: decision‐making; egg laying decision; egg load; information use